National Women Against Pit Closures: gender, trade unionism and community activism in the miners' strike, 1984–5. Issue 1 (2nd January 2018) - Sutcliffe-Braithwaite, Florence; Thomlinson, Natalie
Abstract: This article will offer the first historical assessment of the National Women Against Pit Closures movement. It shows that it was not a spontaneous formation but the result of work by a network of committed, long-time activists with strong connections to the left, including the Communist Party and the Women's Liberation Movement. It will show how key questions caused divisions within the national organisation as it grew. In particular, activists were divided over whether the movement should aim solely to support the strike, or whether it should have broader aims relating to women's lives, gender and feminism. Related to this, the movement divided over relationships with Arthur Scargill and the National Union of Mineworkers, and the question of which women should be allowed to be members. Finally, the article examines how these questions grew more pressing after the end of the strike, and how and why the national movement had largely disappeared three years after the strike.